“How Are My Age and Cows Related?” Cognitive Interviewing as a Tool to Pretest Survey Questions in Two Limited Resource Settings - Wenemark, Marika; Ngwili, Nicholas; Ndoboli, Dickson; Wieland, Barbara; Roesel, Kristina (Frontiers in Veterinary Science, 2022)
Antimicrobial resistance is a complex topic requiring interdisciplinary solutions embedded in One Health thinking. In low-and-middle income settings, research on understanding behaviour and practices related to antimicrobial use in the livestock sector are key. Therefore, to avoid bias in interpreting the data, it is important to design survey tools able to capture underlying complexities while still be clear to interviewers and respondents. This study aims at using cognitive interviews in a respondent-adjusted way that makes it possible to study how survey questions are understood and answered by the respondents. Cognitive interviews may provide a feasible and affordable way of pretesting questionnaires in situations involving many local languages and where time and resources are limited, for example, during a disease outbreak. The results show that even a small number of interviews and using interviewers with limited knowledge of cognitive interviewing can help address many challenges in survey questions and the survey tool.